Adsorption and immobilization of actinides using novel SiO2–ZrO2-calcium alginate aerogels from high level liquid waste. (November 2015) - Zhao, Junchuan; Ding, Xingeng; Meng, Cheng; Ren, Chunrong; Fu, Huiqin; Yang, Hui
Abstract: The novel SiO2 –ZrO2 -calcium alginate aerogels were prepared by Sol–Gel process with phase separation method for investigating the adsorption and immobilization performance of the plutonium and minor actinides from high-level liquid waste (HLLW). The materials contained porous network structure with high surface area (233.44–481.08 m 2 /g) and pore volume (0.50–1.26 m 3 /g). The aerogels were superior adsorbents for the removal of plutonium and minor actinides, the maximum adsorption capacity and adsorption rate (35 °C, 75 rpm) reached 231.5 mg/g and 99.2%. For all the waste forms, SiO2, ZrO2 and Ca2 SiO4 phases were simultaneously observed in the matrix. Moreover, Ce entered into Ca sites of Ca2 SiO4 and Zr sites of ZrO2 . The substitution of Ca and Zr by Ce in the Ca2 SiO4 and ZrO2 implies a promising disposal measure of actinides. Highlights: Novel SiO2 –ZrO2 -calcium alginate aerogels were prepared by Sol–Gel process. The actinides existing in HLLW can be adsorbed and immobilized by the aerogels. The radiotoxicity of HLLW greatly reduced after the adsorption of the aerogels. Geological disposal of actinides is feasible because of the stable waste forms.